Satellite technology : principles and applications - Maini, Anil Kumar; Agrawal, Varsha (Chichester, West Sussex : Wiley, 2014)
Fully updated edition of the comprehensive, single-source reference on satellite technology and its applications Covering both the technology and its applications, Satellite Technology is a concise reference on satellites for commercial, scientific and military purposes. The book explains satellite technology fully, beginning by offering an introduction to the fundamentals, before covering orbits and trajectories, launch and in-orbit operations, hardware, communication techniques, multiple access techniques, and link design fundamentals. This new edition also incl.
3.7.2 Variation in the Orbital Distance3.7.3 Solar Eclipse; 3.7.4 Sun Transit Outrage; 3.8 Eclipses; 3.9 Look Angles of a Satellite; 3.9.1 Azimuth Angle; 3.9.2 Elevation Angle; 3.9.3 Computing the Slant Range; 3.9.4 Computing the Line-of-Sight Distance between Two Satellites; 3.10 Earth Coverage and Ground Tracks; 3.10.1 Satellite Altitude and the Earth Coverage Area; 3.10.2 Satellite Ground Tracks; 3.10.3 Orbit Inclination and Latitude Coverage; Further Readings; Glossary; 4 Satellite Hardware; 4.1 Satellite Subsystems; 4.2 Mechanical Structure; 4.2.1 Design Considerations.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Artificial satellites; Scientific satellites; Artificial satellites; Electrical engineering; Engineering; Scientific satellites; TECHNOLOGY & ENGINEERING -- Engineering (General); Artificial satellites; Scientific satellites; Electronic books